Soleil immatériel : Chemins dans l'art contemporain. - Davvetas, Démosthènes; Delorme, Michel (Paris : Editions Galilée, 1989)
Beuys, Joseph ; Gerz, Jochen ; Baselitz, Georg ; le Gac, Jean ; Basquiat, Jean-Michel ; Boltanski, Christian ; Cucchi, Enzo ; Cragg, Tony ; George et Gilbert ; Twombly, Cy et al.
boek